L-Tryptophan Activates Mammalian Target of Rapamycin and Enhances Expression of Tight Junction Proteins in Intestinal Porcine Epithelial Cells. Issue 6 (15th April 2015) - Wang, Hao; Ji, Yun; Wu, Guoyao; Sun, Kaiji; Sun, Yuli; Li, Wei; Wang, Bin; He, Beibei; Zhang, Qing; Dai, Zhaolai; Wu, Zhenlong
Abstract: Background: Besides serving as a substrate for protein synthesis, L-tryptophan (L-Trp) is used via serotonin-, kynurenine-, and niacin-synthetic pathways to produce bioactive compounds crucial for whole-body homeostasis. It is unknown whether L-Trp itself can regulate metabolic pathways in animal cells. Objective: This study tested the hypothesis that L-Trp may activate mammalian target of rapamycin (mTOR) complex 1 and enhance expression of tight junction (TJ) proteins in intestinal porcine epithelial cells. Methods: Jejunal enterocytes, intestinal porcine epithelial cell line 1 (IPEC-1) isolated from newborn pigs, were cultured in customized Dulbecco's modified Eagle medium (DMEM) supplemented with or without L-Trp for the indicated time periods. Cell proliferation, L-Trp metabolism, protein turnover, mRNA abundance for L-Trp transporters [solute carrier family 3 member 1 ( SLC3A1 ), solute carrier family 6 member 14 ( SLC6A14 ), solute carrier family 6 member 19 ( SLC6A19 ), and Na + /K + ATPase subunit-α1 ( ATP1A1 )], abundance of proteins involved in mTOR signaling, and TJ proteins were determined. Results: L-Trp was not degraded in IPEC-1 cells. Compared with basal medium containing 0.04 mmol/L L-Trp, 0.4 and 0.8 mmol/L LTrp enhanced ( P < 0.05) protein synthesis by 45–52% and cell growth by 17% and 25% on day 1 and 72% and 51% on day 2, respectively, while reducing ( P < 0.05) protein degradation by 12% and 22%, respectively. These effects of L-Trp were associated with mTOR activation and increased ( P < 0.05) mRNA abundance for L-Trp transporters ( SLC6A19, SLC6A14, and SLC3A1 ) by 1.5–2.7 fold and ATP1A1 by 3 fold. L-Trp also upregulated ( P < 0.05) the abundance of occludin, claudin-4, zonula occludens (ZO) 1 and 2 by 0.5–2 fold but did not affect expression of claudin-1 or ZO-3 in IPEC-1 cells. Conclusion: L-Trp is not catabolized by pig small intestinal epithelial cells but can regulate intracellular protein turnover and expression of TJ proteins in these cells.